A survey of prevalent problems of the Bureau of Private Schools area supervisors in the performance of their functions and duties - Valisno, Mona Dumlao 1933- ([Quezon City s.n.], 1965)
This study sought to find out the different problems encountered by area supervisors in the performance of their duties and functions. The different problems in connection to the following are identified: appraisal of private educational institutions, conducting researches on comparative standards of private and professional growth and promotions, investigations of complaints filed against private schools, personnel administration, and public and human relations.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Philippines (Republic) -- Bureau of Private Schools -- School supervision